Credible communication and cooperation: Experimental evidence from multi-stage Games - Andersson, Ola; Wengström, Erik (Journal of economic behavior & organization, 2012)
► This paper experimentally investigates cooperation and non-binding communication in a two-stage game. ► Two treatments are considered: one with only pre-play communication and one where subjects can also communicate intra-play between the stages of the game. ► Pre-play communication has a significantly lower impact on cooperation when intra-play communication is possible. ► The results suggest that the credibility of pre-play messages may depend crucially on future communication opportunities. It is well known that communication often serves as a facilitator for cooperation in static games. Yet, communication can serve entirely different purposes in dynamic settings as communication during the game may work as a means for renegotiation, potentially undermining the credibility of cooperative strategies. To explore this issue, this paper experimentally investigates cooperation and non-binding communication in a two-stage game. More specifically, two treatments are considered: one with only pre-play communication and one where subjects can also communicate intra-play between the stages of the game. The results highlight a nontrivial difference concerning the effects of pre-play communication between the two treatments. Sending or receiving pre-play messages has a positive and significant effect on cooperation if there is no possibility of intra-play communication. However, this effect is significantly reduced when when intra-play communication is allowed. The results suggest that the credibility of pre-play messages may depend crucially on future communication opportunities.